Influencer Reputation, Trust, and Communication Skills as Determinants of Skincare Buying Intention Among Male Models - Mamhot, Francois Rosella; De Marcaida, Francine Therese; Malazarte, Ashley Gwyne; Pimentel, Simon Terrence; Rodrigo, Leonardo Valdoumer; Villones, Keina Karel; Doria, Dave Willie; Ortega, Sergiris (International Journal of Sustainability and Advanced Integrated Research, 2025)
This study examined the influence of social media influencers’ reputations on male models’ buying intentions for skincare products in Cagayan de Oro City. Influencer reputation, treated as the independent variable, was assessed through communication skills and trust, while buying intention served as the dependent variable. A quantitative, descriptive-correlational research design was employed, with data collected through a survey questionnaire. Findings revealed that influencers were perceived as credible, particularly for their trustworthiness and effective communication. These qualities were found to play a meaningful role in shaping skincare product decisions among male models. Also, a focus group discussion was conducted. The FGDs revealed that trust is the primary driver of buying intention, with male models expressing greater confidence in products endorsed by influencers perceived as credible, authentic, and consistent. Participants emphasized that influencers who demonstrate transparency, expertise, and effective communication—such as showing real product use, explaining ingredients, and engaging like consultants rather than salespeople—are more persuasive. Conversely, scripted content, frequent brand-switching, or overtly commercial promotion weakened trust and reduced buying intention. The study concludes that influencer reputation significantly affects consumer buying intention, highlighting the importance of trust and communication in professions centered on appearance, such as modeling. The results provide valuable insights for skincare brands, influencers, and advertising agencies to develop targeted, credible marketing strategies. Future research is recommended to explore additional factors, such as emotional appeal and authenticity cues, better to understand the impact of influencer credibility on consumer behavior.